ISCHEMIC STROKE IN A PATIENT WITH SUSPECTED CERVICAL CANCER: A THERAPEUTIC DILEMMA BETWEEN ANTICOAGULANT OR ANTIPLATELET STRATEGIES IN A RESOURCE-LIMITED SETTING: A RARE CASE REPORT - Yang Yang Endro Arjuna; Vonny Fibrianty Goenawan; Vivien Puspitasari; Yohanes Chandra Kurniawan (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Approximately 5% of strokes with no identifiable cause are linked to previously undiagnosed malignancies. The involvement of multiple vascular territories observed on brain imaging may indicate a hypercoagulable state related to cancer. Early identification is crucial for prompt cancer diagnosis. Case: A 40-year-old woman with no established classic stroke risk factors presented with progressive left-sided weakness and difficulty with speech over three days. She had a history of persistent vaginal bleeding lasting four months. Non-contrast brain CT revealed multiple infarcts affecting the right frontoparietal region, left frontal lobe, and bilateral posterior as well as left anterior internal capsules. An abdominal ultrasound identified a 9.35 × 4.74 cm hypoechoic mass extending from the cervix to the uterus with bladder infiltration, findings highly suggestive of cervical carcinoma. Discussion: Ischemic stroke associated with female reproductive malignancies is rare, with an incidence of around 0.3%. It is mainly caused by cancer-related hypercoagulability due to tumor-derived mucin, procoagulants, and inflammatory cytokines. Multifocal infarcts across various vascular territories may indicate a hypercoagulable state and suggest an underlying malignancy. There is no standardized anticoagulant protocol. Low-molecular-weight heparin (LMWH) is commonly used, though its effectiveness varies. Use of direct oral anticoagulants (DOACs) and antiplatelets is increasing, showing similar safety and efficacy. Conclusion: To date, there is no definitive antithrombotic of choice for cancer-associated ischemic stroke. The selection of antithrombotic therapy should be carefully tailored based on individual risk factors and the patient's clinical condition.